Peningkatan Kesadaran Masyarakat terhadap Bahaya Penggunaan Zat Aditif dalam Makanan - Bialangi, Nurhayati; Musa, Weny J.A; Kilo, Ahmad Kadir; Kurniawati, Erga; Thayban, Thayban (Universitas Negeri Gorontalo, 2023)
Education on the dangers of using food additives is an effort to enhance the public's understanding of the risks associated with consuming foods containing additives. The increased consumption of additives correlates with the rising intake of processed foods. The objective of this community engagement initiative is to raise awareness among the public regarding the potential hazards associated with the use of food additives. The methods employed include lecture-style presentations and discussions. The community gains an understanding of various types of additives commonly used in food, with an emphasis on their benefits, such as prolonging the shelf life of food. However, the education also highlights associated risks, including potential adverse effects on health like allergies, digestive disorders, and long-term effects that are not fully understood. The activities took place in the village of Hutadaa in Gorontalo Regency, with a total of 18 participants. The participants were enthusiastic, and increased knowledge was evident through the questions raised during the session.